Auditory processing in high-functioning adolescents with Autism Spectrum Disorder. - Anne-Marie R DePape (Public Library of Science (PLoS), 2012)
Autism Spectrum Disorder (ASD) is a pervasive developmental disorder including abnormalities in perceptual processing. We measure perception in a battery of tests across speech (filtering, phoneme categorization, multisensory integration) and music (pitch memory, meter categorization, harmonic priming). We found that compared to controls, the ASD group showed poorer filtering, less audio-visual integration, less specialization for native phonemic and metrical categories, and a higher instance of absolute pitch. No group differences were found in harmonic priming. Our results are discussed in a developmental framework where culture-specific knowledge acquired early compared to late in development is most impaired, perhaps because of early-accelerated brain growth in ASD. These results suggest that early auditory remediation is needed for good communication and social functioning.